Metal absorption by pigweed and napier grass in biochar-treated soils - Abdul Kadir Salam; Deva Maharani Wirakrama; Kurnia Rahma Dani; Septi Nurul Aini; Hery Novpriansyah; Supriatin Supriatin (Universitas Sebelas Maret, 2025)
Heavy metal absorption by plants is suggested to be affected by soil treatment with different types of biochar. Due to various types of available biochar materials in the environment, effects of three representative biochar types were evaluated in a greenhouse experiment using polluted soils planted with pigweed (Amaranthus spinosus L.) and napier grass (Pennisetum purpureum Schumach). Soil treatments were conducted with biochar of rice (Oryza sativa)-husk, corn (Zea mays)-cob and cassava (Manihot utilissima)-stem at 10 Mg ha-1. Soils and plants were analysed for Cu and Zn after a 4 weeks plant growth. The results showed that Cu and Zn accumulation by pigweed and napier grass were higher in soils polluted with more Cu and Zn. Pigweed in general acted as phytoextractor, accumulated more Cu and Zn in shoots, while napier grass as phyto-stabilizer, accumulated more Cu and Zn in roots. Pigweed accumulated Cu more effective than napier grass while napier grass more effective in Zn accumulation. Unlike rice-husk or corn-cob, cassava-stem biochar increased the soil Cu and Zn concentrations. Rice-husk and corn-cob enhanced but cassava-stem biochar decreased Cu and Zn accumulation by pigweed and napier grass. Rice-husk and corn-cob biochar showed better potential than cassava biochar for soil Cu and Zn phytoremediation by pigweed and napier grass in heavy-metal polluted tropical soils.